PEMBEAJARAN BERBASIS KETERAMPILAN LITERASI DI SMP NEGERI 1 GANTARANGKEKE - SITTI NURSYAMSI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This research includes research and development which aims to: (1) determine the quality (validity and practicality) of science learning tools based on literacy skills that have been developed (2) determine student responses after being taught using science learning tools based on literacy skills ( 3) find out how effective the achievement of learning outcomes is using science learning tools based on literacy skills. The development of learning devices uses a modified model from Thiagarajan (Four-D), which consists of four stages, namely: (1) identification, (2) design, (3) develop and (4) desiminate (spread). The trial of learning tools was carried out on class VIIA students of SMP Negeri 1 Gantarangkeke, Bantaeng Regency in the 2015/2016 academic year. The data was collected using observation sheets, learning outcomes tests and questionnaires, then the data were analyzed using descriptive analysis techniques. The results of the research on science learning tools based on literacy skills which include: Learning Implementation Plans (RPP), Student Teaching Materials (BAPD), Student Worksheets (LKPD) and Learning Outcomes Tests show that (1) science learning tools based on literacy skills that has been developed to produce valid and practical tools, (2) student responses after being taught using science learning tools based on literacy skills are positive (3) the developed device can provide student learning test results achieving completeness of 87.5% with minimum completeness criteria that must be achieved is 75. Based on these conclusions, it can be stated that the science learning tools based on literacy skills that have been developed can be used in improving student learning outcomes, especially on energy materials in living systems. ABSTRAKPenelitian ini termasuk penelitian pengembangan (research and development) yang bertujuan untuk: (1) mengetahui kualitas (Validitas dan kepraktisan) perangkat pembelajara IPA berbasis Keterampilan literasi yang telah di kembangkan (2) mengetahui tanggapan siswa setelah diajar menggunakan perangkat pembelajaran IPA berbasis keterampilan literasi (3)mengetahui seberapa besar efektifitas pencapaian hasil belajar menggunakan perangkat pembelajaran IPA berbasis keterampilan literasi. Pengembangan perangkat pembelajaran menggunakan model dari Thiagarajan (Four-D) yang di modifikasi,yang terdiri dari empat tahap yaitu: (1) identifikasi (identifity), (2) design (perancangan), (3) develop (pengembangan) dan (4) dessiminate (penyebaran). Uji coba perangkat pembelajaran dilaksanakan pada peserta didik kelas VIIA SMP Negeri 1 Gantarangkeke Kabupaten Bantaeng tahun pelajaran 2015/2016. Pengumpulan data menggunakan lembar observasi, tes hasil belajar dan angket, selanjutnya data dianalisis dengan teknik analisis deskriptif. Hasil penelitian pada perangkat pembelajaran IPA berbasis keterampilan literasi yang meliputi :Rencana Pelaksanaan Pembelajaran (RPP), Bahan Ajar Peserta Didik (BAPD), Lembar Kerja Peserta Didik (LKPD) dan Tes Hasil Belajar menunjukkan bahwa (1) perangkat pembelajaran IPA berbasis keterampilan literasi yang telah dikembangkan menghasilkan perangkat yang valid dan praktis,(2) tanggapan siswa setelah diajar menggunakan perangkat pembelajaran IPA berbasis keterampilan literasi adalah positif (3) perangkat yang dikembangkan dapat memberikan hasil tes belajar peserta didik mencapai ketuntasan sebesar 87,5% dengan kriteria ketuntasan minimum yang harus dicapai adalah 75. Berdasarkan kesimpulan tersebut dapat dikemukakan bahwa perangkat pembelajaran IPA berbasis Keterampilan literasi yang telah dikembangkan dapat digunakan dalam memperbaiki hasil belajar peserta didik khususnya pada materi energi dalam sistem kehidupan.